2017
DOI: 10.3389/fpsyg.2017.00230
|View full text |Cite
|
Sign up to set email alerts
|

Different Measures of Auditory and Visual Stroop Interference and Their Relationship to Speech Intelligibility in Noise

Abstract: Inhibition—the ability to suppress goal-irrelevant information—is thought to be an important cognitive skill in many situations, including speech-in-noise (SiN) perception. One way to measure inhibition is by means of Stroop tasks, in which one stimulus dimension must be named while a second, more prepotent dimension is ignored. The to-be-ignored dimension may be relevant or irrelevant to the target dimension, and the inhibition measure—Stroop interference (SI)—is calculated as the reaction time difference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 59 publications
3
47
0
Order By: Relevance
“…Additionally, the ability to suppress irrelevant information is particularly important for individuals with hearing impairment, in order to filter out lexical information. 67 Inhibition, as assessed by the Flanker, significantly improved for incompatible stimuli. Raw data revealed that the number of correct answers, but not the reaction time, improved.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, the ability to suppress irrelevant information is particularly important for individuals with hearing impairment, in order to filter out lexical information. 67 Inhibition, as assessed by the Flanker, significantly improved for incompatible stimuli. Raw data revealed that the number of correct answers, but not the reaction time, improved.…”
Section: Discussionmentioning
confidence: 93%
“…Although there may be differences in the framing of attentional processes in terms of inhibition or performance monitoring, these imaging results suggest that there may be a connection between constructs of performance monitoring and inhibition as measured by the Stroop task. Individual differences in Stroop-based inhibition scores have been found in at least some studies to relate to speech understanding accuracy, such that listeners with better inhibitory ability (smaller Stroop effects) perform better on speech understanding tasks than listeners with poorer inhibitory ability ( Dey & Sommers 2015 ; Sommers & Danielson 1999 ; Taler et al 2010 ), although this relationship depends on the specifics of the task ( Knight & Heinrich 2017 ).…”
Section: Cognitive Processes Implicated In Comprehending Degraded Spementioning
confidence: 99%
“…For example, Morgan and Brandt (1989) report an auditory Stroop interference effect only in the pitch domain, but not in the time domain. Additionally, Knight and Heinrich (2017) found a modest auditory Stroop interference effect using a gender-based task only on the group level, but could not replicate this effect for every participant or indeed for every one of the four speakers used in their materials.…”
Section: Direct and Conceptual Replications Of Group Effects And Indimentioning
confidence: 86%
“…The visual Stroop task is an example of a task with a rich conceptual replication history, particularly as concerns the testing materials. For example, some studies enhance the visibility of the color by replacing font color with a larger patch of color underneath a superimposed word (Janse, 2012;Knight and Heinrich, 2017). For the control condition, some studies use a string of Xs as their irrelevant characters, while others use unrelated words or even simply blank patches of color (MacLeod, 1991).…”
Section: Direct and Conceptual Replications Of Group Effects And Indimentioning
confidence: 99%